Research on LiDAR technology in early identification of geo-hazards in alpine loess areas. Issue 4 (October 2020) - Wang, L C; Wang, M; Hung, X C; Feng, Z
Abstract: The early identification is a key topic in geo-hazards science in China. Methods including engineering geological analysis, optical RS, InSAR, field survey verification, have been used for early identification of geo-hazards. This paper presents the application of airborne LiDAR to data collection and landslide identification in alpine areas. High-resolution images and point clouds of several landslides were obtained. And the characteristics of landslides have been interpreted. The study of relationship between point clouds and vegetation removal model (VRM) showed that the density of point cloud had a great influence on VRM. The lusher the vegetation, the less point cloud could be collected, resulting in much less point cloud density and lower resolution of VRM. When the density of point cloud is greater than 15 points/m 2, the hillshade map generated after vegetation removal was usable for landslide characteristics recognition. The boundaries, shape, zoning, and some micro-topography, such as cracks with a certain length and width, could be effectively identified. The hillshade map with different azimuth angles were able to visually display the micro-topography features from different orientations. The slope image and surface roughness image from airborne LiDAR provided quantitative topographic parameters for geo-hazards identification, boundaries delineation and volume assessment. In the end, this paper proposes a guidance of early identification of geo-hazards in alpine areas by using LiDAR Technology.